Numerical study on transient effective flow and force areas of reed valve in a rotary compressor. (December 2014) - Tan, Qin; Pan, Shulin; Liu, Zhan; Yu, Xiaoling; Feng, Quanke
Transient effective flow and force areas of reed valve in a rotary compressor are studied by two three-dimensional fluid–structure interaction (FSI) models. One is the full FSI model, the other one is the simplified FSI model, in which the discharge port is not covered. It is apparent that two effects have to be considered in the one-dimensional valve model: partly covered discharge port by the cylinder and the roller, and unsteady flow. In an attempt to describe the first effect, comparison of the transient effective flow and force areas between the full FSI model and the simplified FSI model is presented. For the second effect, unsteady flow and force equations are developed and analyzed, and the steady effective flow and force areas are compared with that of the transient. It is found that if these two effects are negligible, the impact velocity of the valve reed impacting on the retainer will be overestimated.